Longitudinal Assessment of Pain in Rheumatoid Arthritis: Increases in Pain and Their Relationship to Functional Declines and Medication Changes - Hallie M. Altwies; Leah M. Santacroce; Javier Marrugo; Jacklyn Stratton; Jack Ellrodt; Robert S. Rudin; Daniel H. Solomon (ACR Open Rheumatology)
Objective Electronic health applications (apps) allow patients with rheumatoid arthritis (RA) to report patient‐reported outcomes (PROs) between visits. However, almost no data exist on patients’ report of pain between visits and how that correlates with change in function and/or modifications to medication. Methods Patients with RA from one rheumatology practice provided data as part of a study of an app. Patients answered PRO short forms using the app, including the Patient‐Reported Outcomes Measurement Information System pain interference and physical function questionnaires. Each PRO was answered every eight days. We assessed the frequency of significant worsening in pain using the minimally clinically important difference (MCID) of ≥5 points. Logistic regression assessed whether worsening in pain was associated with functional declines and/or RA medication changes. Results Among 150 patients with RA using the app, 83 patients qualified for analysis; the mean age was 62 years, and 82% were female. The median number of pain interference PROs answered per patient was 37 over 52 weeks. Using the first five pain interference PRO responses as the baseline, 60 (72%) patients experienced worsening of at least the MCID, with a median duration of 16 days. The odds ratio (OR) relating significantly worsening pain to declines in function over the next 42 days was 2.71 (95% confidence interval [CI] 1.12–6.89). Worsening pain was not significantly associated with changes to RA medication (OR 1.59, 95% CI 0.62–4.17). Conclusion Clinically significant increases in pain among patients with RA are commonly associated with reductions in function but not with RA medication changes.